Dynamisme, résultats et problèmes actuels de l’agriculture espagnole - Díaz, Victor (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The need to substitute capital for labor-force and the augmentation of internal demand explain the forms of expansion of spanish agriculture for the last 20 years: growth of production and changes in its composition, progression of productivity, intense mecanization, increase of imports more rapidly than exports. To day several factors disturbe this model of growth, the main ones being the slow-down or rural depopulation, the inequality on land distribution, the persistent weakness of breeding. In the crisis ' cycle, we may doubt that government and agricultors can reach, beyond their short term accommodation, a new long term compromise.